Adsorption performance of continuous fixed bed column for the removal of methylene blue (MB) dye using Eucalyptus sheathiana bark biomass - Sen, Tushar; Afroze, Sharmeen; Ang, Ming (Springer, 2015)
In this study, the adsorptive effectiveness of sustainable and cost-effective eucalyptus bark biomass in the removal of methylene blue (MB) dye from its aqueous solution has been tested using a packed bed up-flow column experiment. A series of column experiments using raw eucalyptus bark was performed to determine the breakthrough curves with varying inlet MB dye flow rate (10–15 mL min−1), initial MB dye concentration (50–100 mg L−1) and adsorbent bed height (10–15 cm). High bed height, low flow rate and high initial dye concentration were found to be the better conditions for maximum dye adsorption. To predict the breakthrough curves and to determine the characteristic parameters of the column dynamics for industrial applications and for process design, Thomas model, Yoon–Nelson model and bed depth service time model were applied to experimental breakthrough data. All models were found suitable for describing the dynamic behaviour of the column, with respect to MB flow rate, initial dye concentration and adsorbent bed height. The findings revealed that eucalyptus bark biomass has a high adsorption potential for the removal of MB dye from aqueous solutions in a column system, and that it could be used to treat dye-containing effluents.